Molecular phenotypes of mitochondrial dysfunction in clinically non-manifesting heterozygous PRKN variant carriers - Maria Paulina Castelo Rueda; Alessandra Zanon; Valentina Gilmozzi; Alexandros A. Lavdas; Athina Raftopoulou; Sylvie Delcambre; Fabiola Del Greco M; Christine Klein; Anne Grünewald; Peter P. Pramstaller; Andrew A. Hicks; Irene Pichler (npj Parkinson's Disease, 2023)
Abstract Homozygous or compound heterozygous (biallelic) variants in PRKN are causal for PD with highly penetrant symptom expression, while the much more common heterozygous variants may predispose to PD with highly reduced penetrance, through altered mitochondrial function. In the presence of pathogenic heterozygous variants, it is therefore important to test for mitochondrial alteration in cells derived from variant carriers to establish potential presymptomatic molecular markers. We generated lymphoblasts (LCLs) and human induced pluripotent stem cell (hiPSC)-derived neurons from non-manifesting heterozygous PRKN variant carriers and tested them for mitochondrial functionality. In LCLs, we detected hyperactive mitochondrial respiration, and, although milder compared to a biallelic PRKN-PD patient, hiPSC-derived neurons of non-manifesting heterozygous variant carriers also displayed several phenotypes of altered mitochondrial function. Overall, we identified molecular phenotypes that might be used to monitor heterozygous PRKN variant carriers during the prodromal phase. Such markers might also be useful to identify individuals at greater risk of eventual disease development and for testing potential mitochondrial function-based neuroprotective therapies before neurodegeneration advances.